Costs and Benefits of the Dual Vocational Training System and its Use in the Czech Republic - Provazníková, Romana; Chlebounová, Denisa (Masarykova univerzita, 2019)
Apprenticeship in the Czech Republic suffers from poor quality, low motivation of pupils to complete successfully this type of education, and high unemployment rate of graduates. Dual vocational training system seems to be a possible solution to these problems. This system is increasingly seen as an important educational track that provides youth with the skills necessary for a smooth transition into the labor market. However, the practical part of the dual system provided by companies brings the cost for companies that hire apprentices. Because apprentices become part of a company’s workforce, they also generate a benefit from working productively. The aim of this paper is to analyze costs and benefits of the dual system and to estimate the net costs of training hypothetical company in the Pardubice Region. Based on the resulting net costs of this hypothetical company, company's investment in apprenticeships should start returning in the second year, and the benefits should outweigh the costs in the third and fourth years, too. Further, by correlation and regression analysis, we found that there is a statistically significant influence of length of practice in the company on youth unemployment rate and completion rate of upper secondary school pupils. The importance of time spent in training company has been confirmed.
Náklady a přínosy duálního systému v odborném vzdělávání a jeho využití v České republice
Keywords: dual vocational training system; apprenticeship; costs; benefits; training company; duální systém odborného vzdělávání; učňovské školství; náklady; přínosy; praktické vzdělávání v podniku